Cetomedizzazione e nuove polarità - Palumbo, Mauro; Poli, Stefano (SocietàMutamentoPolitica, 2013)
The article, through the analysis of datasets from Banca d’Italia, explores the ongoing stratification processes in Italian society in contemporary crisis, with particular attention to the evolution of middle and entrepreneurial classes.